A comprehensive review on hybrid power system for PEMFC-HEV: Issues and strategies. (1st September 2018) - Lü, Xueqin; Qu, Yan; Wang, Yudong; Qin, Chao; Liu, Gang
Highlights: The HPS classification of PEMFC-HEV was reviewed. The structures of the HPS system were expressed by drawing intentions. The EMSs of PEMFC-HEV were investigated and studied in recent years. The characteristics of different control strategies were summarized. Abstract: Nowadays, there is a great shortage of non-renewable energy, and the environmental problems such as air pollution caused by automobile exhaust are very serious. The traditional fuel vehicle has been unable to meet the current human needs, so more and more people are concerned about the development of the hybrid electric vehicles (HEVs). Based on proton exchange membrane fuel cell (PEMFC) is a new clean energy without pollution, PEMFC-HEV has a great potential for development. In this review, we have made a comprehensive research on energy management strategy (EMS) of the hybrid power system (HPS) for PEMFC-HEV in recent years. This paper focuses on the EMS of PEMFC as the main power source, the battery and the supercapacitor (SC) as the auxiliary energy in HEV. In this research, the classification of PEMFC-HEV is introduced in detail, and the advantages and disadvantages of various combinations of HPS are summarized. In addition, according to the different requirements and optimization targets of PEMFC-HEV, this paper makes a deep study of the current PEMFC-HEV hybrid system model, and the EMS developed by the researchers. Besides, the simulation and experimental results are compared with each other. From the perspective of strict evaluation, the existing technology can perform more or less. However, high efficiency and optimization performance still fail to achieve high goals. Therefore, the current problems and main control strategies of PEMFC-HEV are discussed and summarized, which is helpful for the development of PEMFC-HEV research in the future. The review will be expected to bring more efforts to the future development of PEMFC-HEV, including faster dynamic response, longer service lifetime, economic optimization, and high efficiency for the PEMFC system.